1913 Ohio Acts 906, ch. 11, §§ 12966-12967 (vol. 103) - (:unkn) unknown (My University, 1913)
Whoever sells of exhibits for sale, to a minor under sixteen years of age, a pistol manufactured of a metallic or hard substance, commonly known as a "toy pistol" or air gun, or any form of explosive gun,shall be fined not less than ten dollars nor more than fifty dollars or imprisoned not less than ten days nor more than twenty days, or both, and be liable in damages to any person injured by such sale. § 12967. Whoever sells, barters, furnishes or gives to a minor under the age of seventeen years, an air-gun, musket, rifle, shotgun, revolver, pistol, or other fire-arm, or ammunition therefor, or, being the owner or having charge or control thereof, knowingly permits it to be used by a minor under such age, shall be fined not more than one hundred dollars or imprisoned in jail not more than thirty days, or both.
Keywords: TRANSFER - MINORS